The effects of biofilm and selective mixed culture on the electricity outputs and wastewater quality of tempe liquid waste based microbial fuel cell - Tania Surya Utami; Rita Arbianti; M Mariana; Nathania Dwi Karina; Vifki Leondo (Reaktor, 2018)
Microbial Fuel Cell (MFC) technology is highly prospective to be developed because it could be utilized as the alternative electricity sources and simultaneously as the wastewater treatment unit using microorganism as catalyst. Industrial Tempe wastewater has the potential to be used as MFC substrate since it still contains high nutrition for microbe and could pollute the environment if it disposed before being processed first. This study focused on investigating the effect of selective mixed culture addition and biofilm formation on the electricity production and the wastewater treatment aspects with tubular single chamber membranless reactor and industrial Tempe wastewater substrate. The result showed that, with the addition of selective mixed culture, the optimum electricity production obtained with addition of 1 ml gram-negative bacteria with increase in electricity production up to 92.14% and average voltage of 17.91 mV, while the optimum decreased levels of COD and BOD obtained with addition of 5 ml gram-negative bacteria which are 29.32% and 51.32%. On the biofilm formation experiment, optimum electricity production obtained from biofilm formation time for 14 days with increase in electricity production up to 10-folds and average voltage of 30.52 mV, while the optimum decreased levels of COD and BOD obtained from biofilm formation time for 7 days which are 18.2% and 35.9%.Keywords : biofilm, Microbial Fuel Cell, selective mixed culture, Tempe wastewater, tubular reactor